Comparative outcomes of robotic, laparoscopic, and open hysterectomy for complex hysterectomy: a retrospective study - Li, Bowei; Ma, Shaohan; Xiong, Zhuo; Chen, Xiuxin; Qi, Xinyi; Ma, Yuan; Li, Ruyue; Zhang, Ruigi; Li, Xinshu; Ha, Chunfang (Frontiers in Surgery, 2026)
BackgroundThe optimal surgical approach for hysterectomy in patients with complex large uteri remains controversial, particularly in those with uterine enlargement and obesity. This study aimed to compare perioperative outcomes and complication rates among three surgical techniques—open abdominal hysterectomy (LH), traditional laparoscopic hysterectomy (TLH), and Da Vinci robot-assisted hysterectomy (DV-RH)—to provide evidence for individualized surgical decision-making.MethodsA retrospective analysis was conducted on 444 patients who underwent hysterectomy for benign gynecological diseases between April 2021 and April 2024 at the Ningxia Medical University General Hospital.Patients were divided into LH (n = 140), TLH (n = 179), and DV-RH (n = 125) groups. Baseline, perioperative indicators, and the incidence of both short- and long-term complications among the three groups were compared. Additionally, BMI was stratified to compare the related indicators separately.ResultsThere were no significant differences in age, BMI, comorbidities, or surgical history among the groups. DV-RH showed significantly lower blood loss (P < 0.001), postoperative VAS scores (P < 0.001), and complication rates, especially in patients with uterine size ≥16 gestational weeks. TLH demonstrated comparable outcomes to DV-RH in selected indicators but had a higher incidence of Clavien-Dindo grade II complications (P = 0.032). Hospitalization costs were highest in the DV-RH group (P < 0.001).ConclusionDV-RH offers superior perioperative outcomes in complex and large uterus cases but incurs higher costs. TLH remains a cost-effective alternative in appropriate patients. Surgical decisions should be based on patient characteristics, technical complexity, and institutional resources.